ASSESSING ENGLISH PRE-SERVICE TEACHERS’ KNOWLEDGE BASE OF TEACHING: LINKING KNOWLEDGE AND SELF-PORTRAYAL - Triastuti, Anita (TEFLIN Journal, 2020)
This study aimed to assess pre-service teachers’ knowledge base of teaching and the extent they perceive and reflect its implementation in a microteaching course. Employing mixed-methods design, the study involved pre-service teachers in a state university in Special Territory of Yogyakarta. The quantitative data were collected from a test on the pre-service teachers’ understanding of teacher knowledge base of teaching and a survey of their perceptions towards the implementation of teacher knowledge base of teaching in their microteaching practices. The qualitative data were gathered from the pre-service teachers’ reflections. The findings showed that despite the overall good test score average of the pre-service teachers’ knowledge base of teaching and the generally positive self-rating perceptions, the pre-service teachers’ limited and descriptive reflections did not sufficiently depict their actual implementation of teacher knowledge base of teaching in their microteaching practices.